The Works of Edgar Allan Poe, The Raven Edition : Table Of Contents And Index Of The Five Volumes - Poe, Edgar Allan, 1809-1849 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Works of Edgar Allan Poe, The Raven Edition" by Edgar Allan Poe is a comprehensive collection of his literary output, likely compiled in the late 19th century. This collection spans various genres, including poetry, essays, and gothic tales, showcasing Poe's distinctive style and exploration of themes like love, death, and the macabre. The book presents significant works such as "The Raven," "The Tell-Tale Heart," "The Fall of the House of Usher," and many others, illustrating Poe's profound influence on American literature and his mastery of suspense and psychological depth. At the start of this collection, the reader is introduced to a preface that sets the stage for understanding Poe's life and literary journey, giving insights into the struggles he faced, both personally and professionally. The subsequent sections outline key works and achievements in his career, detailing his early poetry, notable prose tales, and his lasting impact on both poetry and fiction. The opening expresses deep admiration for Poe's unique genius, highlighting the interplay between his troubled life and his art, thus creating an engaging entry point for readers new to Poe's work or revisiting it with a fresh perspective. (This is an automatically generated summary.)
Release date is 2008-05-19
David Widger and Carlo Traverso
Keywords: Short stories; Fantasy fiction; Horror tales, American; American fiction -- 19th century; Poe, Edgar Allan, 1809-1849; Indexes